2013
DOI: 10.1111/geoa.12014
|View full text |Cite
|
Sign up to set email alerts
|

Internal structure and permafrost characteristics of the rock glaciers of southern carpathians (romania) assessed by geoelectrical soundings and thermal monitoring

Abstract: Six rock glaciers in the Southern Carpathians have been investigated by means of geoelectrical soundings in order to detect their internal stratigraphy and the existence of frozen sediments. In the case of three relict rock glaciers, the electrical resistivity measurements indicated a typical internal structure. Low resistivity values (<10 kΩm) which are typical of unfrozen fine‐grained materials were obtained, but high resistivity values (25–240 kΩm) measured in the Pietroasa, Ieşu and Pietrele rock glaciers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 59 publications
(66 reference statements)
2
17
0
Order By: Relevance
“…The rock glacier is underlain by quartzite bedrock at depths up to >30 m. The bedrock surface has low resistivity (<3,000 Ω·m), indicating the presence of water‐saturated material. Alpine geophysical surveys have similarly observed relatively low resistivities at the base of coarse sediments in rock glaciers (e.g., Evin & Fabre, ; Fisch, Fisch, & Haeberli, ; Ikeda, ; Merz et al, ; Onaca, Urdea, & Ardelean, ), whereas borehole drilling has shown an unfrozen layer of sediments above the bedrock interface in some rock glaciers (Arenson, Hoelzle, & Springman, ; Krainer et al, ; Maurer & Hauck, ). Consequently, it is hypothesized that a saturated zone exists at the interface between the rock glacier and bedrock, which may be within finer sediments over bedrock, or within intensely fractured and weathered rock overlying competent bedrock.…”
Section: Resultsmentioning
confidence: 98%
“…The rock glacier is underlain by quartzite bedrock at depths up to >30 m. The bedrock surface has low resistivity (<3,000 Ω·m), indicating the presence of water‐saturated material. Alpine geophysical surveys have similarly observed relatively low resistivities at the base of coarse sediments in rock glaciers (e.g., Evin & Fabre, ; Fisch, Fisch, & Haeberli, ; Ikeda, ; Merz et al, ; Onaca, Urdea, & Ardelean, ), whereas borehole drilling has shown an unfrozen layer of sediments above the bedrock interface in some rock glaciers (Arenson, Hoelzle, & Springman, ; Krainer et al, ; Maurer & Hauck, ). Consequently, it is hypothesized that a saturated zone exists at the interface between the rock glacier and bedrock, which may be within finer sediments over bedrock, or within intensely fractured and weathered rock overlying competent bedrock.…”
Section: Resultsmentioning
confidence: 98%
“…A C C E P T E D M A N U S C R I P T Langston et al, 2011;McClymont et al, 2011) and rock glaciers (Maurer and Hauck, 2007;Ribolini et al, 2010;Monnier et al, 2011Monnier et al, , 2013Monnier et al, , 2014Onaca et al, 2013, Seppi et al, 2015. Both ice-cored moraines and rock glaciers can be considered as composite and transitional landforms as relicts from former glaciation (cf.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…into active, inactive, and relict types (Sattler et al, 2016). In general, the presence of ice within active and inactive rock glaciers is indicated by a steep (> 35 • ) frontal slope (Ikeda and Matsuoka, 2002), a well-developed flow-like morphology defined by sets of parallel and curved ridges separated by long v-shaped furrows (Barsch, 1996;Roer and Nyenhuis, 2007), and an absence or sparse occurrence of vegetation (Onaca et al, 2013). Inactive rock glaciers also contain ice but are immobile.…”
Section: Rock Glacier Inventory Classification and Databasementioning
confidence: 99%